TINJAUAN YURIDIS SISTEM PEMBUKTIAN DALAM PENANGANAN TINDAK PIDANA KORUPSI DI INDONESIA - Gulo, Efermin; Siregar, Azhali; Ismaidar, Ismaidar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Corruption is an inseparable part of human history and is among the oldest forms of crime, often regarded as one of the diseases of society, similar to other crimes such as theft, which have existed since the dawn of humanity. The main issue faced today is that corruption tends to increase alongside prosperity and technological advancement. Experience shows that as a nation's development progresses, people's needs and desires grow, and one of the consequences may be a greater tendency to commit corrupt criminal acts. This research employs a normative legal method, which refers to legal norms found in statutory regulations, literature, societal legal norms, and relevant data, all of which are analyzed to address the research problems. This study clearly aims to analyze the application of land laws, using a qualitative research approach conducted through examining legal literature and regulations related to the topic of